The Use of English Greetings and Terms of Address by Employees and Homestay Owners in Kintamani Tourism Area, Bali - Pastini, Ni Wayan; Susianti, Hartanti Woro (LACULTOUR: Journal of Language and Cultural Tourism, 2023)
How to communicate properly and correctly is needed by the people of Bali, especially those who live in tourism areas. The increasing arrivals of foreign tourists to the Island of the Gods has made English an important means of communication, which is therefore, badly needed by people in tourist areas, such as the Kintamani. Those who are directly involved in tourism industry activities are expected to provide good service to meet customer satisfaction. This qualitative research, which is based on a phenomenological philosophy approach, aims to determine the understanding of employees and homestay owners in Kintamani on the use of formal English greetings and terms to address customers in their daily tasks. 30 respondents were selected as samples by accidental sampling technique. Meanwhile, data were collected from respondents through interviews and observations, with recording techniques when respondents served guests in eight representative homestays. Furthermore, the data were descriptively analyzed, referring to the basic English grammatical theory. The results of the study show that in general, employees or homestay owners in Kintamani have already understood the formal use of greetings and terms to address the guests in English well. But in daily conversation, they do not use greetings and terms to address guests in formal English which is theoretically appropriate, and prioritize the communicative aspect instead.